Applying a cumulative risk and protective framework to assess early learning in Ghana. Issue 1 (1st January 2023) - Ibekwe-Okafor, Nneka; Wolf, Sharon
ABSTRACT: Many children in developing countries do not acquire functional literacy skills despite being in school. We apply a cumulative risk (aggregate over a range of risk) and protection framework to assess Ghanaian kindergarteners' early academic skills ( N = 1, 852, M(age) = 5.3 years; 50.2% female), considering how family-level risk factors and classroom-level protective factors contribute to the development of early academic skills over one school year. Using multi-level regression analyses, we find that cumulative risk negatively predicts children's early literacy and numeracy skills at the start of kindergarten, as well as literacy skills at the end of the school year controlling for autumn scores. Additionally, high quality teacher–child interactions promote learning regardless of cumulative risk. However, further analyses indicate that classroom quality does not moderate the association between cumulative risk and spring outcomes. Implications for policymakers to engage in a two-generation (targeting parent and child) approach to child development in low- and middle-income countries are discussed.